Analisis Yuridis Independensi Ojk (Otoritas Jasa Keuangan) Dalam Upaya Pengawasan Bank - Ardiansyah, Raden Panji Dandy; , Wardah Yuspin, S.H.,M.Kn.,Ph.D (2017)
The purpose of this research is to describe and determine the form of independency of OJK in bank supervision that OJK apply independency in the task of bank supervision has been set under the act No. 21 of 2011. This research is type of yuridis empirical legal research. The research do with interview in OJK office in Surakarta. The important of independency is for OJK can do duties in the bank supervision optimally and effectively. The independency is necessary in order to OJK can protect, especially supervises intervention of bank as well as form political interference. It is intended that every regulation and supervision peformed by OJK really be objective, without being influenced intervention from the others and to prevent potential conflicts of interest between consumen interact in the financial services sector to achieve the goal of financial stability.